Corelation Behavior of Maintaining Oral and Dental Health With OHI-S Index in SDN 06 Gadut Agam District - Eka Sukanti (Faculty of Public Health, Andalas University, 2017)
Maintenance of teeth in children was still lacking. Simplified Oral Hygiene Index (OHI-S) is influenced by the behavior of maintaining dental and oral health. This study aims to know relationship of the behavior of dental and oral health with the of OHI-S index grader V and VI in elementary school students 06 Gadut Agam 2016. This design study was of analytic with cross sectional method. The population of the research conducted in elementaryÂ grade V and VI school students 06 Gadut Agam, sampling techniques with saturated sampling/research on population. Statistic analysis using Chi-square test. Research results showed the behavior of maintaining dental and oral health with criteria good enough 18 people (51.4%), criteria less 12 people (34.3%) and criteria very good 5 people (14.3%). Students who have an OHI-S middle index 33 people (94.3%) and good indexonly 2 people (5.7%). The results of statistical tests obtained value value = 0.002 (p-value â‰¤ 0.05) have a significant correlation between the behavior of maintaining dental and oral health with OHI-S index in elementary school students 06 Gadut Agam District . Behavior of dental and oral health can be described from the index of OHI-S. It is seen that students consuming sugary foods and sticky without rinse or brush their teeth.